Aramid insulation paper, preparation method and application
Treatment of aramid and cellulose by treating agent A, forming hydrogen bonds and cross-linking structures, solving the insulation problem of aramid insulating paper at high frequency and high temperatures, improving mechanical properties and durability, reducing costs, and providing domestic Alternatives to high-performance aramid insulating paper.
Patent Information
- Application Number
- CN202411423076.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-12
AI Technical Summary
Existing aramid insulating papers are prone to partial discharge and high temperature under high frequency and high temperature conditions, resulting in premature insulation failure and high cost, and it is difficult for domestically to replace foreign high-performance aramid insulating papers.
The meta-aramid chopped fibers and cellulose were treated with treatment agent A. The interaction force between cellulose and aramid fiber was enhanced by forming hydrogen bonds and crosslinking, and the interaction force between cellulose and aramid fiber was prepared with excellent mechanical properties and resistance to high frequency local discharge and resistance to High temperature aramid insulating paper.
It has achieved the improvement of mechanical properties of aramid insulating paper, high-frequency local discharge resistance and high-temperature performance optimization, while reducing costs, and providing the possibility of replacing foreign high-performance aramid insulating paper in China.
Smart Images

Figure BDA0005081395160000091 
Figure BDA0005081395160000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aramid paper, in particular to aramid insulating paper, a preparation method and application thereof. Background Art
[0002] With the advancement of science and technology, the development of electronic and intelligent power systems has led to the challenges of high frequency, high power density, small size and light weight for high-frequency transformers of core electrical equipment. In particular, the power converter connected to the high-frequency transformer has broken through the bottleneck, and the frequency can reach 100kHz or even higher, which will cause the inter-turn insulation of the high-frequency transformer to face more serious field concentration and heat dissipation problems, resulting in premature failure of the inter-turn insulation. Aramid paper, as the main insulating material of high-frequency transformers, is prone to local discharge and local high temperature, causing the insulation of high-frequency transformers to fail prematurely. Therefore, China has adopted various methods to improve the performance of aramid insulation paper and reduce the cost of aramid insulation paper. Plant cellulose has a high aspect ratio and a large specific surface area. The rich hydroxyl groups on the surface can be combined with a variety of substances, which can replace part of the aramid fiber and improve the performance. However, the direct composite performance of cellulose fiber and aramid fiber is poor. In addition, under high voltage conditions, cellulose is flammable and prone to problems such as electrical tree degradation, which seriously affects the mechanical properties and safety performance of aramid insulation paper.
[0003] At present, high-performance aramid insulation paper mainly comes from foreign countries, with high cost and technology blockade. Therefore, in view of the above shortcomings, it is our current direction to obtain aramid fiber composite insulation paper that is resistant to high-frequency partial discharge, high temperature and has comprehensive excellent performance. Summary of the invention
[0004] Based on this, the purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide an aramid insulation paper, a preparation method and an application.
[0005] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing aramid insulation paper, comprising the following steps:
[0006] (1) washing the meta-aramid chopped fibers with a treatment agent A until neutral to obtain a mixed solution, and dispersing the mixed solution with sodium polyacrylate to obtain a slurry suspension; the treatment agent A is at least one of a borate buffer and a boric acid buffer, and the pH value of the treatment agent A is 8.0-11.2;
[0007] (2) adding cellulose to an aminosulfonic acid solution for dispersion, heating for reaction, cooling, centrifugation and precipitation, and washing to obtain activated cellulose;
[0008] (3) mixing the treatment agent A, polyvinyl alcohol and the activated cellulose obtained in step (2), stirring and dispersing them to obtain a cellulose composite slurry;
[0009] (4) The slurry suspension obtained in step (1) and the cellulose composite slurry obtained in step (3) are mixed and dispersed to obtain a mixed slurry, which is dehydrated, formed, and paper-made to obtain the aramid insulation paper.
[0010] The present invention uses treatment agent A to treat meta-aramid short fibers. After treatment with treatment agent A, the amide bonds of the molecular chains on the surface of the aramid fibers are slightly hydrolyzed to generate carboxyl groups and amino groups, which can form hydrogen bonds with the hydroxyl groups on the surface of cellulose. The treatment of the meta-aramid short fibers with treatment agent A changes their microscopic morphology and chemical structure. Some spherical microstructures appear on the smooth surface of the meta-aramid short fibers, and the surface roughness is significantly increased. The treatment of the meta-aramid short fibers with treatment agent A can further enhance the crosslinking between the meta-aramid short fibers.
[0011] The present invention utilizes treating agent A and aminosulfonic acid to jointly treat cellulose. The -NH2 bond in aminosulfonic acid can form a new hydrogen bond with the -OH bond on the plant fiber, thereby strengthening the interaction between cellulose molecules, enhancing the strength and toughness of cellulose, and at the same time, enhancing the thermal stability of cellulose.
[0012] The inventors found in actual experimental processes that by using cellulose treated with treatment agent A and aminosulfonic acid in combination with meta-aramid chopped fibers treated with treatment agent A, aramid insulating paper with excellent mechanical properties and resistance to high-frequency partial discharge and high temperature can be obtained.
[0013] The inventors found in the actual experiment that when the pH is greater than 8, it is more conducive to the distribution of boron on the surface of aramid fiber, improving the dispersibility of aramid fiber in the solution; however, when the pH is too high, greater than 11.2, boron is enriched, affecting the carboxyl and amino groups on its surface to form hydrogen bonds with the hydroxyl groups on the surface of cellulose. Therefore, when the pH is between 8.0-11.2, the aramid fiber has a good dispersion effect in the finished paper, and does not affect the hydrogen bond formation of the surface groups, thereby improving the tensile strength and electrical strength.
[0014] Preferably, in step (1), the borate buffer is one of borax-potassium dihydrogen phosphate buffer, borax-calcium chloride buffer, and borax-sodium carbonate buffer, and the boric acid buffer is one of boric acid-potassium chloride buffer and boric acid-potassium hydroxide buffer.
[0015] Preferably, in the step (1), the treatment agent A is treated at 20°C-35°C for 1h-2h; in the slurry suspension, the mass percentage of sodium polyacrylate is 0.1%-10%, the mass percentage of meta-aramid chopped fibers is 5%-10%, and the deflaking is treated at 20°C-35°C for 0.5h-2h.
[0016] Preferably, in step (2), the aminosulfonic acid solution is prepared using solvent 1, and solvent 1 is at least one of water, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide.
[0017] Preferably, in step (2), the mass percentage of the aminosulfonic acid solution is 1wt%-15wt%; and the mass ratio of the cellulose to the aminosulfonic acid is (10-50):(1-5).
[0018] Preferably, in step (2), the cellulose is at least one of bamboo pulp cellulose, bagasse pulp cellulose, bacterial cellulose, short cotton linter cellulose and microcrystalline cellulose.
[0019] Preferably, the dispersion time is 5 min-60 min; the heating reaction temperature is 60°C-100°C, and the heating reaction time is 1 h-24 h; the centrifugal speed is 2000 r / min-8000 r / min, and the centrifugal time is 5 min-10 min; the washing solvent is at least one of water, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide.
[0020] Preferably, in step (3), the mass ratio of the treatment agent A, polyvinyl alcohol and the activated cellulose obtained in step (2) is treatment agent A: polyvinyl alcohol: activated cellulose obtained in step (2) = (1-30): (1-10): (60-98).
[0021] Preferably, in step (4), the absolute dry mass of the cellulose composite pulp is 2%-10% of the absolute dry mass of the mixed pulp.
[0022] Preferably, in the step (4), the rotation speed of the mixing and dispersing is 2500 r / min-5000 r / min; the temperature of the papermaking is 100° C.-200° C., the pressure is 8.0 MPa-10.0 MPa, and the time is 10 min-30 min.
[0023] In addition, the present invention provides aramid insulation paper prepared by the preparation method of aramid insulation paper.
[0024] Furthermore, the present invention provides application of the aramid insulation paper in the field of transformers.
[0025] Compared with the prior art, the beneficial effects of the present invention are:
[0026] The present invention uses treatment agent A to treat meta-aramid short fibers. After treatment with treatment agent A, the amide bonds of the molecular chains on the surface of the aramid fibers are slightly hydrolyzed to generate carboxyl groups and amino groups, which can form hydrogen bonds with the hydroxyl groups on the surface of cellulose. The treatment of the meta-aramid short fibers with treatment agent A changes their microscopic morphology and chemical structure. Some spherical microstructures appear on the smooth surface of the meta-aramid short fibers, and the surface roughness is significantly increased. The treatment of the meta-aramid short fibers with treatment agent A can further enhance the crosslinking between the meta-aramid short fibers.
[0027] The present invention utilizes treating agent A and aminosulfonic acid to jointly treat cellulose. The -NH2 bond in aminosulfonic acid can form a new hydrogen bond with the -OH bond on the plant fiber, thereby strengthening the interaction between cellulose molecules, enhancing the strength and toughness of cellulose, and at the same time, enhancing the thermal stability of cellulose.
[0028] The inventors found in actual experimental processes that by using cellulose treated with treatment agent A and aminosulfonic acid in combination with meta-aramid chopped fibers treated with treatment agent A, aramid insulating paper with excellent mechanical properties and resistance to high-frequency partial discharge and high temperature can be obtained. DETAILED DESCRIPTION
[0029] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. Its purpose is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise specified, the experimental reagents and instruments designed for the implementation and comparative examples of the present invention are all commonly used ordinary reagents and instruments, which can be obtained from commercial channels. In the implementation and comparative examples, the experimental methods used are conventional methods unless otherwise specified; and unless otherwise specified, the raw materials used in parallel experiments are the same batch of raw materials.
[0030] A method for preparing aramid insulating paper comprises the following steps:
[0031] (1) treating the meta-aramid chopped fibers with a treatment agent A at 20° C. to 35° C. for 1 h to 2 h, washing to neutrality to obtain a mixed solution, and dispersing the mixed solution with sodium polyacrylate at 20° C. to 35° C. for 0.5 h to 2 h to obtain a slurry suspension;
[0032] The pH value of the treatment agent A is 8.0-11.2; the treatment agent A is at least one of a borate buffer and a boric acid buffer, the borate buffer is one of a borax-potassium dihydrogen phosphate buffer, a borax-calcium chloride buffer, and a borax-sodium carbonate buffer, and the boric acid buffer is one of a boric acid-potassium chloride buffer and a boric acid-potassium hydroxide buffer;
[0033] In the slurry suspension, the mass percentage of sodium polyacrylate is 0.1%-10%, and the mass percentage of meta-aramid chopped fibers is 5%-10%;
[0034] (2) adding cellulose to a 1wt% to 15wt% aminosulfonic acid solution for dispersion, heating for reaction, cooling, centrifugation and washing to obtain activated cellulose;
[0035] The mass ratio of cellulose to aminosulfonic acid is (10-50):(1-5);
[0036] The aminosulfonic acid solution is prepared using solvent 1, wherein solvent 1 is at least one of water, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide;
[0037] The cellulose is at least one of bamboo pulp cellulose, bagasse pulp cellulose, bacterial cellulose, short cotton linter cellulose and microcrystalline cellulose.
[0038] Preferably, the dispersion time is 5 min-60 min; the heating reaction temperature is 60°C-100°C, and the heating reaction time is 1 h-24 h; the centrifugal speed is 2000 r / min-8000 r / min, and the centrifugal time is 5 min-10 min; the washing solvent is at least one of water, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide.
[0039] (3) mixing the treatment agent A, polyvinyl alcohol and the activated cellulose obtained in step (2), stirring and dispersing them to obtain a cellulose composite slurry;
[0040] The mass ratio of the treatment agent A, polyvinyl alcohol, and the activated cellulose obtained in step (2) is treatment agent A: polyvinyl alcohol: activated cellulose obtained in step (2) = (1-30): (1-10): (60-98);
[0041] (4) The slurry suspension obtained in step (1) and the cellulose composite slurry obtained in step (3) are mixed and dispersed at a rotation speed of 2500 r / min-5000 r / min to obtain a mixed slurry, which is dehydrated, formed, and paper-made at a temperature of 100°C-200°C, a pressure of 8.0 MPa-10.0 MPa, and a time of 10 min-30 min to obtain the aramid insulating paper.
[0042] The absolute dry mass of the cellulose composite pulp is 2%-10% of the absolute dry mass of the mixed pulp.
[0043] Examples and Comparative Examples
[0044] Raw materials: bamboo pulp cellulose: degree of polymerization 780, cellulose content greater than 85%, Beijing Northern Century Cellulose Technology Development Co., Ltd.; bagasse pulp cellulose: industrial grade (bleached), Nanning Sugar Co., Ltd. Sugar and Paper Factory; bacterial cellulose: diameter 50-100nm, Guilin Qihong Technology Co., Ltd.
[0045] Example 1
[0046] A method for preparing aramid insulating paper comprises the following steps:
[0047] (1) treating the meta-aramid chopped fibers with a treatment agent A at 25° C. for 2 h, washing them to neutrality to obtain a mixed solution, and dispersing the mixed solution with sodium polyacrylate at 25° C. for 2 h to obtain a slurry suspension;
[0048] The pH value of the treatment agent A is 11.0; the treatment agent A is a borax-sodium carbonate buffer;
[0049] In the slurry suspension, the mass percentage of sodium polyacrylate is 3%, and the mass percentage of meta-aramid short fibers is 5%;
[0050] (2) adding cellulose to a 3 wt % aminosulfonic acid solution for dispersion, heating for reaction, cooling, centrifuging and precipitating, and washing to obtain activated cellulose;
[0051] The mass ratio of cellulose to aminosulfonic acid is 30:5;
[0052] The aminosulfonic acid solution is prepared using solvent 1, which is N,N-dimethylformamide;
[0053] The cellulose is bamboo pulp cellulose.
[0054] Preferably, the dispersion time is 10 min; the heating reaction temperature is 100° C., and the heating reaction time is 2 h; the centrifugal speed is 8000 r / min, and the centrifugal time is 5 min; and the washing solvent is N,N-dimethylformamide.
[0055] (3) mixing the treatment agent A, polyvinyl alcohol and the activated cellulose obtained in step (2), stirring and dispersing them to obtain a cellulose composite slurry;
[0056] The mass ratio of the treatment agent A, polyvinyl alcohol, and the activated cellulose obtained in step (2) is treatment agent A: polyvinyl alcohol: activated cellulose obtained in step (2) = 5:5:90;
[0057] (4) The slurry suspension obtained in step (1) and the cellulose composite slurry obtained in step (3) are mixed and dispersed at a rotation speed of 2500 r / min to obtain a mixed slurry, which is dehydrated, formed, and paper-made at a temperature of 100° C., a pressure of 10.0 MPa, and a time of 30 min to obtain the aramid insulating paper.
[0058] The absolute dry mass of the cellulose composite pulp is 2% of the absolute dry mass of the mixed pulp.
[0059] Example 2
[0060] A method for preparing aramid insulating paper comprises the following steps:
[0061] (1) treating the meta-aramid chopped fibers with a treatment agent A at 35° C. for 1 h, washing them to neutrality to obtain a mixed solution, and dispersing the mixed solution with sodium polyacrylate at 35° C. for 0.5 h to obtain a slurry suspension;
[0062] The pH value of the treatment agent A is 11.0; the treatment agent A is a borax-sodium carbonate buffer;
[0063] In the slurry suspension, the mass percentage of sodium polyacrylate is 5%, and the mass percentage of meta-aramid short fibers is 5%;
[0064] (2) adding cellulose to a 10 wt% aminosulfonic acid solution for dispersion, heating for reaction, cooling, centrifuging and precipitating, and washing to obtain activated cellulose;
[0065] The mass ratio of cellulose to aminosulfonic acid is 10:1;
[0066] The aminosulfonic acid solution is prepared using solvent 1, which is dimethyl sulfoxide;
[0067] The cellulose is bagasse pulp cellulose.
[0068] The dispersion time is 60 minutes; the heating reaction temperature is 60° C., and the heating reaction time is 24 hours; the centrifugal speed is 6000 r / min, and the centrifugal time is 6 minutes; the washing solvent is dimethyl sulfoxide.
[0069] (3) mixing the treatment agent A, polyvinyl alcohol and the activated cellulose obtained in step (2), stirring and dispersing them to obtain a cellulose composite slurry;
[0070] The mass ratio of the treatment agent A, polyvinyl alcohol, and the activated cellulose obtained in step (2) is treatment agent A: polyvinyl alcohol: activated cellulose obtained in step (2) = 5:5:90;
[0071] (4) The slurry suspension obtained in step (1) and the cellulose composite slurry obtained in step (3) are mixed and dispersed at a rotation speed of 3000 r / min to obtain a mixed slurry, which is dehydrated, formed, and paper-made at a temperature of 200° C., a pressure of 8.0 MPa, and a time of 10 min to obtain the aramid insulating paper.
[0072] The absolute dry mass of the cellulose composite pulp is 2% of the absolute dry mass of the mixed pulp.
[0073] Example 3
[0074] A method for preparing aramid insulating paper comprises the following steps:
[0075] (1) treating the meta-aramid chopped fibers with a treatment agent A at 30° C. for 1.5 h, washing them to neutrality to obtain a mixed solution, and dispersing the mixed solution with sodium polyacrylate at 30° C. for 1 h to obtain a slurry suspension;
[0076] The pH value of the treatment agent A is 11.0; the treatment agent A is a borax-sodium carbonate buffer;
[0077] In the slurry suspension, the mass percentage of sodium polyacrylate is 10%, and the mass percentage of meta-aramid short fibers is 5%;
[0078] (2) adding cellulose to a 15 wt% aminosulfonic acid solution for dispersion, heating for reaction, cooling, centrifuging and precipitating, and washing to obtain activated cellulose;
[0079] The mass ratio of cellulose to aminosulfonic acid is 30:5;
[0080] The sulfamic acid solution is prepared using solvent 1, solvent 1 dimethyl sulfoxide;
[0081] The cellulose is bacterial cellulose.
[0082] The dispersion time is 50 minutes; the heating reaction temperature is 70° C., and the heating reaction time is 18 hours; the centrifugal speed is 8000 r / min, and the centrifugal time is 5 minutes; the washing solvent is dimethyl sulfoxide.
[0083] (3) mixing the treatment agent A, polyvinyl alcohol and the activated cellulose obtained in step (2), stirring and dispersing them to obtain a cellulose composite slurry;
[0084] The mass ratio of the treatment agent A, polyvinyl alcohol, and the activated cellulose obtained in step (2) is treatment agent A: polyvinyl alcohol: activated cellulose obtained in step (2) = 5:5:90;
[0085] (4) The slurry suspension obtained in step (1) and the cellulose composite slurry obtained in step (3) are mixed and dispersed at a rotation speed of 3000 r / min to obtain a mixed slurry, which is dehydrated, formed, and paper-made at a temperature of 150° C., a pressure of 8.0 MPa, and a time of 10 min to obtain the aramid insulating paper.
[0086] The absolute dry mass of the cellulose composite pulp is 2% of the absolute dry mass of the mixed pulp.
[0087] Example 4
[0088] Compared with the preparation method of the aramid insulating paper in Example 1, the only difference is that the selection of the treating agent A in the step (1) is different. Specifically, the pH value of the treating agent A is 9.6; the treating agent A is a boric acid-potassium chloride buffer solution; the remaining components, weight parts and preparation methods are exactly the same.
[0089] Example 5
[0090] Compared with the preparation method of the aramid insulating paper in Example 1, the only difference is that the selection of the treating agent A in the step (1) is different. Specifically, the pH value of the treating agent A is 8.0; the treating agent A is a borax-calcium chloride buffer solution; the remaining components, weight parts and preparation methods are exactly the same.
[0091] Example 6
[0092] Compared with the preparation method of aramid insulation paper in Example 1, the only difference is that the mass percentage of meta-aramid chopped fibers in the slurry suspension in step (2) is 10%; the other components, weight parts and preparation methods are exactly the same.
[0093] Example 7
[0094] Compared with the preparation method of the aramid insulation paper in Example 1, the only difference is that in step (3), the mass ratio of treatment agent A: polyvinyl alcohol: activated cellulose obtained in step (2) is 15:10:75; the remaining components, weight parts and preparation methods are exactly the same.
[0095] Example 8
[0096] Compared with the preparation method of aramid insulation paper in Example 1, the only difference is that the absolute dry mass of the cellulose composite slurry in step (4) is 5% of the absolute dry mass of the mixed slurry; the other components, weight parts and preparation methods are exactly the same.
[0097] Example 9
[0098] Compared with the preparation method of aramid insulation paper in Example 1, the only difference is that the absolute dry mass of the cellulose composite slurry in step (4) is 10% of the absolute dry mass of the mixed slurry; the other components, weight parts and preparation methods are exactly the same.
[0099] Comparative Example 1
[0100] Compared with the preparation method of the aramid insulating paper in Example 1, the only difference is that the selection of the treatment agent A in the step (1) is different. Specifically, the pH value of the treatment agent A is 11.0; the treatment agent A is a sodium phosphate-disodium hydrogen phosphate buffer solution; the remaining components, weight parts and preparation methods are exactly the same.
[0101] Comparative Example 2
[0102] Compared with the preparation method of the aramid insulating paper in Example 1, the only difference is that the selection of the treatment agent A in the step (1) is different. Specifically, the pH value of the treatment agent A is 7.6; the treatment agent A is potassium dihydrogen phosphate-sodium hydroxide buffer solution; the remaining components, weight parts and preparation methods are exactly the same.
[0103] Comparative Example 3
[0104] Compared with the preparation method of the aramid insulating paper in Example 1, the only difference is that the selection of the treating agent A in the step (1) is different. Specifically, the pH value of the treating agent A is 6.0; the treating agent A is an acetic acid-sodium acetate buffer solution; the remaining components, weight parts and preparation methods are exactly the same.
[0105] Comparative Example 4
[0106] Compared with the preparation method of aramid insulation paper in Example 1, the only difference is that the absolute dry mass of the cellulose composite slurry in step (4) is 1% of the absolute dry mass of the mixed slurry; the other components, weight parts and preparation methods are exactly the same.
[0107] Comparative Example 5
[0108] Compared with the preparation method of aramid insulation paper in Example 1, the only difference is that the absolute dry mass of the cellulose composite slurry in step (4) is 15% of the absolute dry mass of the mixed slurry; the other components, weight parts and preparation methods are exactly the same.
[0109] Performance Testing
[0110] The thickness, tensile strength and electrical strength are tested in accordance with GB / T 29627.2-2013 "Polyaramid fiberboard for electrical use Part 2: Test methods" and GB / T20629.3-2019 "Non-cellulose paper for electrical use Part 3: Unfilled polyaramid fiber paper".
[0111] The test results are shown in Table 1.
[0112] Table 1
[0113]
[0114]
[0115] It can be seen from the above table that the aramid composite insulating paper prepared in the embodiment of the present invention has a tensile strength of more than 50 MPa and an electrical strength of more than 25 kV / mm. The present invention uses cellulose treated with treatment agent A and aminosulfonic acid in combination with meta-aramid short fibers treated with treatment agent A to obtain aramid insulating paper with excellent mechanical properties and resistance to high-frequency partial discharge and high temperature.
[0116] From the comparison between Example 1, Examples 4-5, and Comparative Examples 1-3, it can be seen that when the pH value of the treatment agent A is 8.0-11.2, the tensile strength and electrical strength of the prepared aramid composite insulating paper are better.
[0117] By comparing Example 1, Example 8-9, and Comparative Examples 4-5, it can be seen that when the absolute dry mass of the cellulose composite slurry in step (4) is 2%-10% of the absolute dry mass of the mixed slurry, the tensile strength and electrical strength of the aramid composite insulating paper finally prepared are both high. When the proportion of cellulose is too small, the tensile strength and electrical strength are seriously reduced. When the proportion of cellulose is too high, the cellulose content is too much, and the cellulose itself has a negative impact on the tensile strength and electrical strength. Therefore, the inventor found in the actual experimental process that when the absolute dry mass of the cellulose composite slurry is 2%-10% of the absolute dry mass of the mixed slurry, the tensile strength and electrical strength of the aramid composite insulating paper finally prepared are both high.
[0118] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing aramid insulation paper, characterized in that: The following steps are involved: (1) washing the meta-aramid chopped fibers with a treatment agent A until they are neutral to obtain a mixed solution, and dispersing the mixed solution with sodium polyacrylate to obtain a slurry suspension; The treatment agent A is at least one of a borate buffer and a boric acid buffer, and the pH value of the treatment agent A is 8.0-11.2; (2) adding cellulose to an aminosulfonic acid solution for dispersion, heating for reaction, cooling, centrifugation and precipitation, and washing to obtain activated cellulose; (3) mixing the treatment agent A, polyvinyl alcohol and the activated cellulose obtained in step (2), stirring and dispersing them to obtain a cellulose composite slurry; (4) The slurry suspension obtained in step (1) and the cellulose composite slurry obtained in step (3) are mixed and dispersed to obtain a mixed slurry, which is dehydrated, formed, and paper-made to obtain the aramid insulation paper.
2. The method for preparing aramid insulating paper according to claim 1, characterized in that: In the step (1), the borate buffer is one of borax-potassium dihydrogen phosphate buffer, borax-calcium chloride buffer, and borax-sodium carbonate buffer, and the boric acid buffer is one of boric acid-potassium chloride buffer and boric acid-potassium hydroxide buffer.
3. The method for preparing aramid insulation paper according to claim 1, characterized in that: In the step (1), the treatment agent A is treated at 20°C-35°C for 1h-2h; in the slurry suspension, the mass percentage of sodium polyacrylate is 0.1%-10%, the mass percentage of meta-aramid short fibers is 5%-10%, and the deflaking is treated at 20°C-35°C for 0.5h-2h.
4. The method for preparing aramid insulation paper according to claim 1, characterized in that: In the step (2), the mass percentage of the aminosulfonic acid solution is 1wt%-15wt%; the mass ratio of the cellulose to the aminosulfonic acid is (10-50):(1-5).
5. The method for preparing aramid insulation paper according to claim 1, characterized in that: In the step (3), the mass ratio of the treatment agent A, polyvinyl alcohol, and the activated cellulose obtained in the step (2) is treatment agent A: polyvinyl alcohol: activated cellulose obtained in the step (2) = (1-30): (1-10): (60-98).
6. The method for preparing aramid insulation paper according to claim 1, characterized in that: In the step (4), the absolute dry mass of the cellulose composite pulp is 2%-10% of the absolute dry mass of the mixed pulp.
7. The method for preparing aramid insulation paper according to claim 1, characterized in that: In the step (4), the rotation speed of mixing and dispersing is 2500r / min-5000r / min; the temperature of the papermaking is 100°C-200°C, the pressure is 8.0MPa-10.0MPa, and the time is 10min-30min.
8. Aramid insulating paper prepared by the method for preparing aramid insulating paper according to any one of claims 1 to 7.
9. Use of the aramid insulation paper as claimed in claim 8 in the field of transformers.
Citation Information
Patent Citations
High-strength high-flame-retardant aramid insulation paper as well as preparation method and application thereof
CN117758547A
Cellulose-based flameproof and bulking converted sheet
JP1991130499A